Answer:
11 hours 30 minutes
Step-by-step explanation:
3 + 4x - 3x = 4 Given
3 + (4x - 3x) = 4
3 + x = 4 Combine like terms
3 - 3 + x = 4 - 3
x = 1 Subtraction Property of Equality
A group of students was asked about the number of e-mails they each sent that day. The results are: 0,0,0,0,1,2,2,3,5,5, 8, 9, 1
masha68 [24]
Answer:
Step-by-step explanation: I don’t know I’m sorry
Answer:
C) 2 (2x + 3) (3x + 1)
Step-by-step explanation:
12x² + 22x + 6
2 ( 6x² + 11x + 3 )
2 [ 6x² + 9x + 2x + 3 ]
2 [ 3x ( 2x + 3 ) + 1 ( 2x + 3 ) ]
2 ( 2x + 3 ) ( 3x + 1 ) ⇒ C
Answer:
C
Step-by-step explanation:
divide 14 by 4 to solve it, you get 3.5 or 3 1/2